DNA analyses reveal abundant homoplasy in taxonomically important morphological characters of Eusiroidea (Crustacea, Amphipoda). (22nd December 2015) - Verheye, Marie L.; Martin, Patrick; Backeljau, Thierry; D'Udekem D'Acoz, Cédric
Abstract : Eusiroidea is one of the 20 amphipod superfamilies that were erected to subdivide the very large and controversial suborder Gammaridea. Yet, the definition of the superfamily is not based on synapomorphies, but on a combination of diagnostic phenetic similarities that hold more or less consistently across families. Moreover, many of the characters used to define eusiroid families are suspected to show convergent evolution. The current classification of the Eusiroidea may therefore not reflect evolutionary relationships accurately. Here, we present a molecular phylogenetic re‐analysis of the Eusiroidea based on a comparison of 18S and 28S rDNA sequences of 73 species, representing 47 genera and 16 families that potentially belong to the superfamily. The results suggest that at least species belonging to 14 of these traditional families would be part of a eusiroid clade, increasing by more than twofold the species and generic richness of the group. However, most of the eusiroid families surveyed do not appear monophyletic. Finally, the analyses show that several important morphological characteristics, traditionally used in eusiroid taxonomy, are homoplastic.